How to earn dollars overseas - Andres, Tomas Quintin D. (Quezon City New Day, 1994)
This book contains realistic advice combined with creative attitudes and techniques for overseas job seekers. It not only provides instructions on learning about available overseas jobs but also gives facts and data about conditions abroad and how to cope with loneliness and "culture shock" once they are there.
This book is product of more than 25 years in counseling and human resource development and training experience of the author. This book was written as a practical tool for the many Filipino workers and professionals as well as students and graduates in their search for overseas jobs. In this book, realistic advice combined with creative attitudes and techniques for overseas job seekers are given. It not only provides instructions on learning about available overseas jobs but also gives facts and data about conditions abroad and how to cope with loneliness and "culture shock"once there.
Contents: Preparing for an overseas jobs. Matching and qualifications with jobs. Pointers to consider in applying. How to apply. Interview, testing, selection. Dos and don'ts. Details before departure. Managing foreign exchange earnings. Appendix. Bibliography. About the author.
Purpose: "To serve as a practical tool for the many Filipino workers and professionals as well as students and graduates in their search for overseas jobs."
Keywords: Vocational guidance -- Philippines -- Handbooks, manuals, etc; Job hunting -- Philippines -- Handbooks, manuals, etc